Produksi Program Radio “Jateng Pagi” di RRI PRO 1 Semarang (Pengarah Acara) - Josinita Endah Juniarlin; Lintang Ratri Rahmiaji (Interaksi Online, 2018)
Radio Republik Indonesia is the oldest radio in Indonesia and the only government-owned radio that has the vision to realize Indonesia's public broadcasting institution as the largest networked radio, nation character builder, world-class. RRI has very wide network from Aceh to Papua. However, there are still many young people who do not know Radio Republik Indonesia. The number of private radios emerging has made RRI's popularity waning. The main reason is the image of RRI as a radio news and radio for parents, so less attractive for young people who are thirsty for entertainment and the latest things. One solution is to re-concept or re-create "Jateng Pagi" talk show program with a new concept by involving students as resource persons in this program and targeting the youth as the target audience, so it is expected to increase radio audience especially RRI PRO 1 Semarang. During the program's execution, the author served as a creative director who re-created “Jateng Pagi”. The results of the post-production questionnaire showed through the production of "Jateng Pagi", the team succeeded in increasing the number of listeners of "Jateng Pagi" RRI PRO 1 Semarang to 81 listeners. Similarly, at first the active listeners only 3 pepople in each episode, with the new concept now "Jateng Pagi" managed to increase 8 to 19 active listeners in each episode